OH SAY CAN YOU SAY DI-NO-SAUR? All about Dinosaurs - WORTH, BONNIE (HARPERCOLLINS CHILDREN'S BOOKS HONG KONG, 2001)
Dr. Seuss's Cat in the Hat shows Sally and Dick how dinosaur fossils are excavated, assembled, and displayed in a museum
Shelving Location "J"